Growth response of plantations Hippophae rhamnoides Linn. on different slope aspects and natural Caragana opulens Kom. to climate and implications for plantations management - Cunwei Che; Shengchun Xiao; Aijun Ding; Xiaomei Peng; Jingrong Su (Ecological Indicators, 2022)
Dendroecology is an effective way to measure the radial growth of plants under different environmental conditions, since the results may provide implications for plantations management. In this study, we examined the growth response of planted shrub Hippophae rhamnoides on different slope aspects and scattered distributed natural Caragana opulens to climate in the western Loess Plateau. The results show that insufficient precipitation from April to June is the main limiting factor of planted H. rhamnoides growth in the western Loess Plateau. On different slope aspects, the H. rhamnoides was susceptible limited by precipitation and drought stress on shady slopes than sunny slopes, with precipitation model explaining 53.0 % of radial growth variation on shady slopes and 30.6 % of growth variation on sunny slopes. Planting density is the main reason for the above phenomenon. Sufficient precipitation and moderate planting density (around 3300 shrubs per hectare) may mitigate the limitations of drought on planted H. rhamnoides growth. In addition, the growth of natural C. opulens was less affected by precipitation and drought stress compared to the planted H. rhamnoides in same region, precipitation and drought model explaining only 14.6 % and 10.5 % of growth variation, respectively, this may promotion appropriately as a suitable afforestation species in the western Loess Plateau. Therefore, the slope aspects, planting density, as well as the limiting factors and time on growth of plantation species should be full considered to vegetation restoration in the future, and thereby, improve the stability and sustainable development of plantation forests in the western Loess Plateau.